The Implementation of IoT on Supply Chain Management Information System - Ishlah, Aanisah Waliy; Erni, Erni; Juhanda, Juhanda; Kristianes, Kristianes; Hakim, Muhammad Arif Rahman; Tannady, Hendy (Journal of Social Science and Business Studies, 2025)
In the increasingly advanced digital era, the Internet of Things (IoT) has become a key element in industrial transformation, especially in supply chain management information systems. This study aims to explore the implementation of IoT in improving the efficiency and effectiveness of the supply chain in the manufacturing sector. Using a literature review approach, this study identifies various IoT applications, such as sensor networks, Radio Frequency Identification (RFID) technology, and cloud computing that have made significant contributions to real-time data collection, asset tracking, and inventory management. The results of the study indicate that IoT implementation not only improves operational efficiency but also strengthens the competitiveness of companies through automation and artificial intelligence-based data analysis. IoT has been proven to optimize production processes, improve supply chain visibility, and reduce operational costs. However, challenges such as device interoperability, cybersecurity, and resistance to technological change are still major barriers to IoT adoption. This study also highlights the importance of collaboration between IoT solution providers, technology experts, and policy makers to create an ecosystem that supports innovation. The right implementation strategy, accompanied by comprehensive workforce training and a collaborative approach, are needed to maximize the potential of IoT.